TRANSULNAR TECHNIQUE AMONG PATIENTS UNDERGONE PERCUTANEOUS CORONARY INTERVENTIONS: A STUDY ON ASSOCIATED COMPLICATIONS - NAWAZ, T; HUSSAIN, S; AMIN, M; ALI, H; SAJJAD, W (Biological and Clinical Sciences Research Journal, 2024)
The objective of this observational study, conducted at the Department of Cardiology in LRH, Peshawar from June 2023 to December 2023, was to assess the complications associated with the transulnar technique in patients undergoing percutaneous coronary interventions (PCI) for ischemic heart disease. A total of 110 patients were included in this study. All patients underwent PCI with the transulnar technique, and complications were assessed post-procedure. The mean age of the patients was 58.75±7.05. The complications observed were minor bleeding in 20 patients (18.2%), ulnar artery occlusion in 9 patients (8.2%), hematoma in 6 patients (5.5%), and stroke in 2 patients (1.8%). The transulnar technique is an effective modality for patients undergoing PCI in terms of complications such as minor bleeding, ulnar artery occlusion, hematoma, and stroke.